The duty of loyalty in the cooperative law. A comparative study - Villafañez Pérez, Itziar (REVESCO. Revista de Estudios Cooperativos, 2015)
Among the duties of the government bodies’ members of the different entities, which are connected to the good government, the duty of loyalty must be underlined. This duty, derived from the good-faith duty, obliges to act in the interest of the entity in case of conflict of interest, and to subordinate one’s own interests, except when there is an authorisation. Loyalty duty is applicable both to managers, who must manage the entity’s interest, and to partners, according to the common purpose derived from the company contract. This duty, at the same time, includes some particular rules, referred to transparency, remuneration, prohibition of competition, self-contracting... This essay compares the regulation of the duty of loyalty and its realizations in the different Cooperative Laws in Spain, both referring to the managers and to the partners, comparing this, at the same time, with the regulation of these aspects in companies’ general legislation, an in the Spanish Corporate Enterprises Act in particular, in order to obtain a general view of the issue, a necessary basis to go more deeply into it, and suggesting some preliminary conclusions or assessments.
Keywords: conflict of interest; transparency; good faith; managers; members.